2018
DOI: 10.3892/ol.2018.8042
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the mitochondrial chaperone tumor necrosis factor receptor‑associated protein 1 is associated with the poor prognosis of patients with colorectal cancer

Abstract: Tumor necrosis factor receptor-associated protein-1 (TRAP-1), a mitochondrial chaperone, contributes significantly to the progression of cancer. However, the understanding of its involvement in the clinicopathological characteristics and prognosis of colorectal cancer (CRC) remains limited. The aim of the present study was to assess the significance of TRAP-1 expression in CRC. The expression of TRAP-1 was evaluated in corresponding cancerous, paracancerous, lymph node and distant metastatic tissues of 256 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
(50 reference statements)
0
7
0
Order By: Relevance
“…Interestingly, the upregulation of TRAP1 expression has different effects in different cancers, exhibiting a dual effect of carcinogenesis 72,73 or cancer inhibition 74 . Clinical experiments have shown that overexpression of TRAP1 is connected to a poor prognosis in CRC patients 75 . Apart from that, TRAP1 can regulate glycolysis metabolism and help reverse the resistance of CRC patients to EGFR inhibitors 76 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the upregulation of TRAP1 expression has different effects in different cancers, exhibiting a dual effect of carcinogenesis 72,73 or cancer inhibition 74 . Clinical experiments have shown that overexpression of TRAP1 is connected to a poor prognosis in CRC patients 75 . Apart from that, TRAP1 can regulate glycolysis metabolism and help reverse the resistance of CRC patients to EGFR inhibitors 76 .…”
Section: Discussionmentioning
confidence: 99%
“…While these studies identify TRAP1 as cytoprotective in mitochondrial-associated neuropathologies, other studies have highlighted a potential pro-neoplastic role of TRAP1 in cancer, where it can also display cytoprotective and other pro-tumorigenic activities. Thus, TRAP1 expression was found to be increased in hepatocellular carcinoma [ 47 ], breast cancer [ 48 ], glioma [ 49 ], small cell lung cancer [ 50 ], and kidney, prostrate, ovarian, colorectal, and esophageal cancer, and it is correlated with advanced-stage metastatic tumors with poor prognosis [ 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. In colorectal cancer and its animal models, increased TRAP1 expression was found to be localized to pro-neoplastic lesions in the tumor [ 58 , 59 ].…”
Section: Trap1: Cytoprotective or Pro-neoplastic?mentioning
confidence: 99%
“…In colorectal cancer and its animal models, increased TRAP1 expression was found to be localized to pro-neoplastic lesions in the tumor [ 58 , 59 ]. While data supporting the importance of TRAP1 are numerous [ 24 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 59 , 60 ], these findings are challenged by other reports where TRAP1 expression inversely correlates with tumor stage [ 19 ] or is seemingly unimpactful in carcinogenesis models in TRAP1 knockout (KO) mice [ 61 ]. This has led to a general consensus that TRAP1’s role may be more context dependent.…”
Section: Trap1: Cytoprotective or Pro-neoplastic?mentioning
confidence: 99%
See 1 more Smart Citation
“…Promising diagnostic and prognostic tools in human CRCs are reviewed in [ 67 , 68 , 69 ]. TRAP1 expression is higher in tumour tissues compared to surrounding non-malignant tissues, and elevation of TRAP1 protein levels and gene copy number correlate with malignant progression and metastasis of colorectal carcinoma [ 70 , 71 , 72 ]. TRAP1 is also known to affect mitochondrial architecture and dynamics, where TRAP1 knockdown favours mitochondrial fusion, while TRAP1 overexpression induces mitochondrial fission and subsequently enhanced migration in vitro and in tumour metastasis in vivo [ 73 ].…”
Section: Associated Mitochondrial Mutations and Dysfunctionsmentioning
confidence: 99%